(untitled) (Lex localis - Journal of Local Self-Government, 2025)
This paper conducts a critical analysis of the judicial treatment of superstitious practices in India, with a particular emphasis on whether these practices are classified as protected cultural or religious heritage or as unconstitutional violations of fundamental rights. The Essential Religious Practice Doctrine, a judicial tool developed by the Supreme Court to identify which religious practices warrant protection under Article 25 of the Constitution of India, is the framework within which the study is framed. The research delves into the intricate relationship between religious freedom and fundamental rights, with a particular emphasis on Article 21, which ensures the right to life and personal dignity. Superstition-driven practices, such as ritual sacrifice, black magic, witch-branding, and gender-based exclusion, frequently assert religious or cultural legitimacy. However, they frequently violate constitutional protections by compromising personal autonomy, Essential Religious Practice perpetuating discrimination, or endangering health. A nuanced approach has been developed by Indian courts, which differentiate between practices that are essential to faith and those that are social evils disguised as religion. The judiciary’s delicate balance between enforcing constitutional morality and protecting religious identity is exemplified by landmark cases such as Shirur Mutt, Sabarimala, and Haji Ali Dargah. The study employs a doctrinal research methodology, utilizing constitutional provisions, judicial decisions, legislative measures such as the Maharashtra Anti-Superstition Act, and secondary scholarly literature to trace the evolving judicial discourse. The results indicate that Indian courts are increasingly rejecting harmful superstitious practices as non-essential to religion and unconstitutional when they violate life, dignity, equality, or morality, despite an initial reluctance to intervene in matters of faith. The paper emphasizes the judiciary’s critical role in balancing the protection of fundamental rights and religious freedom in a pluralistic society.